LITERARY CONSTRUCTION, HEROIC INFLATION, AND THE QUESTION OF HISTORICITY: REASSESSING THE VIRĀṬA EPISODE IN THE MAHĀBHĀRATA - Mr Varun Gupta (IJRDO - Journal of Social Science and Humanities Research, 2026)
In the *Mahabharata*, the episode of the cattle-raid on Virata is widely recognized—both among the general public and within academic circles—as a prime illustration of Arjuna's martial prowess and as a foundational backdrop for the Kurukshetra War. In this research paper, this prevailing perception is re-examined by shifting the analytical focus from the narrative's outcome to its underlying structural composition. Drawing upon a study of various manuscripts, textual stratification theory, internal narrative analysis, and comparative epic studies, this paper elucidates the specific function of the Virata War within the broader narrative architecture of the *Mahabharata*.Rather than viewing this episode merely as a factual reenactment of a historical event, this analysis highlights its inherent structural characteristics—such as the intensification of heroic sentiments, narrative compression, rhetorical exaggeration, and the strategic deployment of symbolism. From this perspective, the Virata War may be conceptualized as a 'transitional narrative unit'; a unit that serves to re-establish the *Kshatriya* identity of the Pandavas following their period of exile, while simultaneously prefiguring the narrative trajectory and moral intensity of the ensuing Kurukshetra War.By employing linguistic evidence alongside narrative and comparative methodologies, this research paper offers a significant contribution to the existing body of literature concerning the compositional process, historicity, and diverse interpretive paradigms of the *Mahabharata*.